Networks in the Hellenistic world: according to the pottery in the Eastern Mediterranean and beyond - Fenn, Nina; Römer-Strehl, Christiane (BAR / International series, 2013)
"This volume contains papers presented at the international conference 'Networks in the Hellenistic world - according to the pottery in the Eastern Mediterranean and beyond' which took place at the universities of Cologne and Bonn 23rd-26th February 2011. The organizers, all specialists in Hellenistic pottery of different regions in the Eastern Mediterranean, invited participants working from the Adriatic Sea to Asia Minor and up to Central Asia to consider their material according to the common platform of networks and exchange systems."--Publisher's web site